Comparison of Isosorbide Mononitrate (IMN) Plus Misoprostol Versus Misoprostol Alone in Post-Term Pregnancies - Sana Nazir, Sadaf Ishfaq, Rabia Tahir, Shabnam Tariq, Sara Munir (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: compare mean induction to delivery interval in patients induced with isosorbide mononitrate (IMN) plus misoprostol versus misoprostol alone in post-term pregnancies. Methodology: To conduct this Randomized Controlled Trial at Social Security Hospita, MNCH, Lahore, we enrolled 150 patients (75 patients in each group) and randomly separated them into two groups of similar size. Group A had IMN (40mg) injected into the posterior fornix of the vagina, followed by misoprostol (50ug), while Group B received misoprostol (50ug) alone was induced. After the initial dose, second doses were only administered if labour was not started or regular uterine contractions had not been started within six hours of the first dose. A maximum of four doses were administered at six-hour intervals until the patient entered the active phase and gave birth. A pre-designed proforma was added to record the average time from induction to delivery. Patients’ age, parity, and number of doses of misoprostole were stratified to adjust for possible effect moderators. Results: In our study, 62.67% of the cases (n=47) in A Group and 56% (n=42) in B Group were in range of 18 and 25, while 37.33 percent (n=28) in A Group and 44 percent (n=33) in B Group were in range of 26 and 35, with mean+sd calculated as 24.4+5.06 and 25.25+5.53 years, respectively. Mean time of induction to delivery was 19.28+1.75 in A Group and 23.75+2.47 mins in B Group. Conclusion: Patients induced with isosorbide mononitrate (IMN) and misoprostol had a considerably shorter induction-to-delivery time than those treated with misoprostol alone.